1999
DOI: 10.1142/s0217984999000634
|View full text |Cite
|
Sign up to set email alerts
|

INTEGRABLE BOUNDARY CONDITIONS FOR THE q-DEFORMED EXTENDED HUBBARD MODEL

Abstract: Integrable open-boundary condition for the q-deformed Essler-Korepin-Schoutens extended Hubbard model of strongly correlated electrons are studied in the framework of the boundary quantum inverse scattering method. Diagonal boundary K-matrices are found and nine classes of integrable boundary terms are determined. PACS Number(s): 71.20.Fd, 75.10.Jm, 75.10.LpOne-dimensional strongly correlated electron systems with boundaries are of great importance because of their promising role in theoretical condensed matte… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
18
1

Year Published

1999
1999
2015
2015

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(24 citation statements)
references
References 18 publications
5
18
1
Order By: Relevance
“…15, except that Ford et al 14 found an adsorption energy of −0.81 eV for top NO at 0.25 ML due to the perpendicular configuration employed in their study. The present results are slightly different previous results, 11,12,15,16 which are mainly due to the differences in computational parameters. For example, three-layer slab was used in Ref.…”
Section: B Energeticscontrasting
confidence: 99%
See 2 more Smart Citations
“…15, except that Ford et al 14 found an adsorption energy of −0.81 eV for top NO at 0.25 ML due to the perpendicular configuration employed in their study. The present results are slightly different previous results, 11,12,15,16 which are mainly due to the differences in computational parameters. For example, three-layer slab was used in Ref.…”
Section: B Energeticscontrasting
confidence: 99%
“…The identification of the bonding strength and adsorption site preferences of the mentioned molecular species on TM surfaces is crucial in obtaining an atom-level picture of catalytic activities. The adsorption of NO on the Pt͑111͒ surface has been widely addressed in experimental [3][4][5][6][7][8][9][10] and theoretical studies, [11][12][13][14][15][16][17] however, even for this apparent "simple" and well-defined system, several questions remain open and in debate. In this work, we will report a systematic investigation of the adsorption of NO on the Pt͑111͒ surface employing first-principles calculations.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Pt, C, and O pseudopotentials have been tested for the platinum bulk and for isolated CO molecular properties and in previous calculations. 23,24 At 500 eV plane wave cutoff, the calculated CO bond length, bond energy, and harmonic frequency are 1.138 Å, 11.39 eV, and 2200 cm Ϫ1 , respectively, and are in good agreement with experimental results ͑1.128 Å, 11.12 eV, and 2170 cm Ϫ1 25 ͒. The GGA calculated lattice constant of 3.968 Å for Pt was used in the calculations.…”
supporting
confidence: 67%
“…The N-O and N-Pt surface distances of 1.225 and 2.045 Å, respectively, were adopted according to the work of Ge and King. 35 The molecular orbitals used for the CI calculation were determined by restricted Hartree-Fock calculations of the cationic cluster, NO-Pt 9 + . We used the CDW-type broken-symmetry HF solution, because the symmetric orbitals showed singlet instability.…”
Section: Transition Dipole Moments Of Substrate-to-substrate and Smentioning
confidence: 99%